(untitled) (Élisée - Revista de Geografia da UEG, 2021)
The municipality of Bahía de Banderas is constantly exposed to large tourism investments that degrade its natural resources. This article studies the actions of two civil associations that work to strengthen the municipality’s resilience to this phenomenon: Mujeres Unidas por Bahía de Banderas and Alianza Jaguar A.C. For this study, members of the organizations were interviewed on how they have addressed the problems caused by tourism. In addition, the urbanization carried in the bay towns was analyzed through field trips. With the collected information, a group was formed and the methodologies that successfully strengthened resilience in the communities were identified. Finally, the analysis of the two associations showed that there are other ways to promote human rights-centered economic development.